Omega-3 as an Anti-Inflammatory Modality: Literature Review - Hidayat, Rachmat; Nur Riviati (Biomedical Journal of Indonesia, 2021)
A B S T R A C TOmega-3 fatty acids are polyunsaturated fatty acids that have multiple double bonds,the first double bond is located on the third carbon atom of the omega-methyl group,the next double bond is located at the third carbon atom from the previous doublebond. The methyl omega group is the last group in the fatty acid chain. Omega-3 fattyacids are nutrients that play a vital role in the growth and development process ofbrain neuron cells for the intelligence of the born baby.